PENERAPAN DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIIB SMP BEER SEBA PEKANBARU - Martha Febriani Br Sitinjak; Atma Murni; Nahor Murani Hutapea (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research based on the students’ math achievement on grade VIIIB of SMP Beer Seba Pekanbaru which under the minimum completeness criteria with percentage 32.14% for math test with linear equations systems of two variables topic and 28.57% for Pythagoras's Theorem topic. The research is classroom action research. The research aims to improve the math learning process and improve math learning result at grade VIIIB of SMP Beer Seba Pekanbaru with applying the discovery learning. The research subjects were students of class VIIIB SMP Beer Seba Pekanbaru which consists of 15 boys and 14 girls in the even semester of 2015/2016 academic years. The instruments of data collection were observation sheets and students’ math achievement tests. The observation sheets were analyzed in desciptive narative and the students’ math achievement tests were analyzed in statistic desciptive. The result of descriptive narative had showed an improvement of learning process prior to the action on the first cycle and from the first cycle to the second cycle. The result of statistic descriptive had showed an increasing number of students’ math achievement from the basic score to the first math test with percentage 22.78% and from the first math test to the second math test with percentage 3.58%. So, the result of this research showed that the implementation of discovery learning can improve the learning process and improve the students’ math achievement for grade VIIIB SMP Beer Seba Pekanbaru in the even semester of 2015/2016 academic years.Key Word : Students’ Math Achievement, Discovery Learning, Clasroom Action Research